Mr. and Mrs Doug Murray (Raton, New Mexico Raton Range, 1978)
Newspaper Article on Mr. and Mrs. Doug Murray driving to Denver for their son who arrived 8 hours late at the Denver Airport.
Master list item #: 62
File location is in the Raton File Cabinet
Keywords: Murray, Doug; Murray, (Mrs.); Murray, J.D.; Collegiate Wood Band Group; Kennedy Airport; Denver Airport; Local History; Biography; Life and Customs; Flying; Travel; Airport; Delays; Raton, New Mexico; Denver, Colorado; Europe